Ankle-joint mobility and standing squat posture in elite junior cross-country skiers. A pilot study - Conradsson, D.; Friden, C.; Nilsson-Wikmar, L.; Äng, B. O. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: Skating technique in cross-country skiing is a complex multi-joint movement with kinematics comparable to those of the standing squat exercise where any restricted joint mobility in the lower extremity-chain may change the movement pattern. The aim of this pilot study was to investigate the effect of ankle mobility on trunk posture during squat exercise in cross-country skiers. METHODS: Seven elite junior cross-country skiers (age range 17-19 years) performed two different standing squats, one with hands on hips and one with arms extended above the head. The squats were recorded on video and analyzed in selected positions: 90° and maximal knee flexion. Segment angles for shank and trunk were calculated from anatomical references relative to vertical/horizontal orientation in space. Recordings from passive ankle dorsiflexion were correlated with 1) trunk flexion, and 2) angle index (trunk flexion relative to shank angle). RESULTS: Reduced ankle dorsiflexion was moderately associated with increased trunk flexion with hands on hips (r=-0.51 to -0.57), and arms above head (r=-0.61 to -0.64). Further, reduced dorsiflexion was also moderately associated with decreased angle index with hands on hip (r=0.60 to 0.67) but highly associated with decreased angle index with arms above head (r=0.75 to 0.76). CONCLUSION: The results imply that reduced ankle dorsal mobility is related to decreased angle index as well as increased trunk flexion during squat exercise, thus indicating the relevance of good ankle joint mobility for appropriate upper-body posture during squat exercise.